Nonlinear Static Pushover Evaluation of the Performance of the Faculty of Nursing Building at the University of Timor with ASCE 41-17 - Resky, Yoseph Satrio; Zacharias, Hendry David; Siahaya, Rivaldo (Fakultas Teknik Universitas Tanjungpura, 2026)
The Faculty of Nursing Building at Universitas Timor is a critical academic facility designed in accordance with SNI 1726:2019 and SNI 2847:2019. Despite compliance with these standards, its structural capacity and seismic performance have not been thoroughly verified. This study evaluates the building’s structural behavior using a nonlinear static pushover approach. Structural data were derived from design drawings and modeled in ETABS to simulate seismic demands for 250- and 1000-year return periods. Section-level nonlinear behavior was examined using XTRACT and ETABS Section Designer to define plastic hinge properties and overstrength factors. The results demonstrate that the building’s lateral capacity exceeds the seismic demand for both hazard levels. Performance assessment based on interstory drift limits prescribed by ASCE 41-17 indicates Immediate Occupancy (IO) for the 250-year earthquake and Life Safety (LS) for the 1000-year earthquake. However, the predicted collapse mechanism is undesirable, as initial yielding occurs in the column elements. Overall, the structure exhibits satisfactory seismic capacity and performance.